Controlled trial of chlorpromazine as antisecretory agent in patients with cholera hydrated intravenously. Issue 6326 (8th May 1982) - Rabbani, G H; Greenough, W B; Holmgren, J; Kirkwood, B
Abstract : A randomised controlled trial was conducted to investigate the ability of chlorpromazine to reduce intestinal secretion in cholera. Chlorpromazine had reduced loss of intestinal fluid in animals with diarrhoea induced by cholera toxin, and in a preliminary study the drug had reduced purging in patients with cholera. Forty-six adults with cholera were included in the randomised trial. Of these, 34 were treated with chlorpromazine (1 mg/kg or 4 mg/kg either by mouth or intramuscularly) and 12 served as controls. After treatment with the drug there was a significantly greater reduction in the rate of fluid loss in the treated patients than in the controls during the first (p less than 0.005), second (p less than 0.05), and fourth (p less than 0.01) eight-hour periods, but not during the third eight-hour period; the dose of 4 mg/kg was only marginally more effective than 1 mg/kg. The effect of chlorpromazine was strikingly biphasic, with one peak during the first eight hours and another 24-32 hours after administration. Chlorpromazine also significantly reduced the duration of diarrhoea, frequency of vomiting, and amount of intravenous fluid required. The drug induced mild sedation and no hypotension in these well-hydrated patients. These findings confirm the effectiveness of chlorpromazine in reducing fluid loss in cholera. A sedative effect, however, especially in children, may limit its usefulness and requires further study.